Strategies for High End High Rise Residential Property Using Marketing Mix during a Soft Market in Kuala Lumpur - Alias, Anuar; Al Sadat Zyed, Zafirah; Sze Ning, Chong (International Journal of Property Sciences (E-ISSN: 2229-8568), 2018)
Developers face challenges and issues to sell properties when soft market happens. Thus, effective strategies must be identified to reach out to potential buyers. According to the information obtained from National Property Information Centre (NAPIC), the percentage of overhang and unsold high end high rise residential properties in Kuala Lumpur experienced drastic increase in recent years. The aim of this study is to identify developer’s strategies within the marketing mix for high end high rise residential property in soft property market. This study is designed to investigate feedback of house buyers in Kuala Lumpur towards developer’s strategies implemented in soft property market. Questionnaire survey was adopted in this study. The questionnaire is designed in accordance to buyers’ perspective on developer’s strategies based on the “Marketing Mix” which consists of price, product, place and promotion. The respondents’ feedback is important for the analysis of developer’s strategies. The findings show that when soft market happens, the features of the product are the most important factor in house purchase. Therefore, the elements under product should be focused to complement other segments of marketing mix especially price strategy.